The Effect of Providing Counseling With Audiovisual Methods on the Knowledge of Mothers of Toddlers about Stunting - Nisa, Setia; Prasetyaningsih (PT Inovasi Pratama Internasional, 2022)
Indonesia is included in the 5 countries with the highest stunting rate of children under five, namely there are 7.5 million children under five. Based on the results of the 2016 Basic Health Research (Riskesdas), the prevalence of stunting nationally was 37.2%, which means an increase compared to 2010 (35.6%) and 2007 (36.8%). Based on data from the Pariaman City Health Office from 7 existing Puskesmas working areas, the Marunggi Health Center Work Area Pariaman City has the highest percentage of very short children growth, reaching 63 people out of 772 toddlers (8.2%) and 108 people short (14%) ).This research uses a correlation pre-experimental design with the One Group Pretest-Posttest Design, which is a research design that has a pretest before being given treatment. Thus it can be known more accurately, because it can be compared with being held before being given treatment. The sample of this study used a purposive sampling technique with certain criteria with the number of samples obtained by 50 PUSH women. The results of the study will be analyzed using the independent sample t test (paired sample t-test. The results of statistical tests obtained P value = 0.000. This means that there is a significant difference in the average knowledge of mothers of children under five before and after counseling. This research is expected to be evidence based, become a guide or material for health promotion at the Marunggi Health Center, as a material for public consideration of the importance of knowledge about stunting.